НЕКОТОРЫЕ ИТОГИ РАБОТЫ ТЕРАПЕВТИЧЕСКОЙ СЛУЖБЫ КУРСКОЙ ОБЛАСТИ НА СОВРЕМЕННОМ ЭТАПЕ РАЗВИТИЯ СИСТЕМЫ ЗДРА ВОО ХРА НЕНИЯ - О. И. Гончарова; В. П. Михин; Н. Г. Филиппенко (Архивъ внутренней медицины, 2012)
Therapeutic service of Kursk region is represented in more than 500 medical practitioners. It participates in the regional target programs in the federal programs, continually improve their work, organize not only medical, but also preventive care to the population. This article presents the characteristics and results of therapeutic service of Kursk region in recent years.